(untitled) (Journal of the College of Basic Education, 2022)
The problem of the research lies in the fact that there are conflicting problems in the performance of educational supervisors towards teachers in these schools, and on top of them are the supervisory practices of educational supervisors. Identifying these practices and standing by them in order to find the best ways to improve these supervisory practices and behaviors, not to mention the importance of these topics that deal with basic aspects of the educational process, given that supervisory methods are among the most important pillars of the basic work of the educational supervisor in their educational institutions